Synthesis and Characterization of Some Capsaicin Derivatives and Study their Pharmacological Hydrolysis - Faris Hamood Mohammed (Journal of Global Pharma Technology, 2018)
One of the alkaloid compounds that were found in the fruit of the Capsicum genus is a Capsaicin, which provides its spicy flavor. Capsaicin extracted directly from fruit and limited use in clinical trials to support the biological activity. In this research, using cationic polymerization were carried out to the synthesis of drug-spacer polymer to obtain more able as hydrolysis proceeded and more convenient for hydrolysis of attachment of the appropriate pendant drugs, through increases the distance between drugs as a bioactive and backbone of the polymer chains. All prepared drug polymers were characterized by FTIR, UV-visible, TGA and 1HNMR techniques.